Polarization-anisotropy of mid-infrared emission properties of Er3+ ions in YAlO3 crystal – INVITED - Nady Ahmed; Cassouret Florent; Loiko Pavel; Normani Simone; Braud Alain; Chen Weidong; Petrov Valentin; Sun Dunlu; Zhang Peixiong; Viana Bruno; Hideur Ammar; Camy Patrice (EPJ Web of Conferences, 2023)
We report on a polarization-resolved study of mid-infrared emission properties of Er3+ ions in the orthorhombic YAlO3 crystal. For the 4I11/2 → 4I13/2 transition, σSE reaches 0.20×10-20 cm2 at 2919 nm (for light polarization E || c). Pump-induced polarization switching between the E || b and E || c eigen-states is observed in an 10 at.% Er:YAlO3 laser. Pumped by an Yb-fiber laser at 976 nm, this laser delivers 0.77 W at 2919 nm with a slope efficiency of 31.4% being close to the Stokes limit and a laser threshold of 33 mW.